Emily Dowdey: capstone - Dowdey, Emily, artist (Colorado State University. Libraries, 2025)
The artist's statement: Beginning my art career at a young age, storytelling has always been my main objective. I have always strived to create visual narratives that evoke emotion and empathy, inviting viewers to connect with the figures I depict on a personal level. Whether it's a poster, book cover, or anything else, I aim to tell stories that feel alive and emotionally valuable. I am equally fascinated by the discipline of drawing and hold the techniques I have learned over time incredibly valuable to my practice. Figure drawing is a central focus in my work. The human figure is incredibly expressive, and I find exploring the human condition through the creative process can be a powerful way to create empathy and connection between my art and others. As I have worked with a graphic design concentration, digital illustration consists of the bulk of my work. Through this, I have kept my traditional drawing background at the core of what I make and is often a driving force in my inspiration. Sketching and brainstorming is my favorite part of everything I do, as I have found that it is the most authentic aspect of every project, showing not only what can I create, but also inviting mistakes to happen, as these often lead to the best outcomes. This fluidity in how I view my work has allowed me to form a style that is sincere yet playful. I encourage all viewers of my undergraduate work to see past the destination and enjoy the journey.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design